Irreversible electroporation in the treatment of locally advanced pancreas and liver metastases of colorectal carcinoma - Wichtowski, Mateusz; Nowaczyk, Piotr; Kocur, Jacek; Murawa, Dawid (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Irreversible electroporation is a new, non-thermal ablation technique in the treatment of parenchymal organ tumors which uses short high voltage pulses of electricity in order to induce apoptosis of targeted cells. In this paper the application of this method of treatment in locally advanced pancreatic cancer (LAPC) and liver cancer is analyzed. Material and methods : Between 04.2014 and 09.2014 two patients with LAPC and one with colorectal liver metastasis (CRLM) were qualified for treatment with irreversible electroporation. Both patients remained under constant observation and control. PubMed/Medline, Embase and Google Scholar databases were searched and eight original reports on irreversible electroporation of pancreatic and liver tumors based on the biggest groups of patients were found. Results : Two patients with LAPC and one with CRLM were qualified for ablation with irreversible electroporation. In all three patients a successful irreversible electroporation (IRE) procedure of the whole tumor was conducted. In the minimum seven-month follow-up 100% local control was achieved – without progression. In the literature review the local response to treatment ranged from 41% to 100%. The event-free survival rate in six-month observation was 94%. Conclusions : Ablation with irreversible electroporation is a new non-thermal ablation technique which has been demonstrated, both in the previously published studies and in the cases described in this paper, as a safe and efficient therapeutic method for patients with LAPC and CRLM.